Earnings Virality - Campbell, Brett; Drake, Michael; Thornock, Jacob; Twedt, Brady (Journal of Accounting and Economics, 2023)
We examine the determinants and market consequences associated with earnings announcements going viral on social media, a phenomenon we label “earnings virality.” Using a comprehensive panel of historical Twitter data, we find that the typical earnings announcement receives relatively little social media coverage, but others go viral on social media, quickly reaching the feeds of millions of people. We find that viral earnings announcements generally have Twitter content that is more extreme in tone and contains less unique content. Further, earnings virality is positively associated with revenue surprises, investor recognition, retail investor ownership, and retail investor trading around the announcement. Earnings virality appears to be detrimental to markets, as it coincides with lower market liquidity and slower price formation. Overall, our evidence suggests that user-driven dissemination through social media platforms, when amplified and taken to extreme levels, may be harmful to markets.